MAIN EYEOLOGICAL FACTORS OF KSEROSTOMY - N.O. Ryabushko; V.M. Dvornik (Ukrainian Medical Stomatological Academy, 2018)
Dry mouth has recently become a widespread problem. Mouthwash plays an important role in protecting against caries, chewing and eating. Insufficient salivation leads to mucosal dryness and discomfort. Dry mouth, caused by a decrease or cessation of secretion of the salivary glands, is called xerostomia. Patients suffering from xerostomia feel anxious because of itching and burning ("burning mouth syndrome"), taste disturbance, difficulty in talking and swallowing food (especially dry), difficulty in wearing removable prostheses that injure the mucous membrane of the mouth. The main clinical signs associated with hypofunction of the salivary glands include loss of gloss of the mucous membrane of the mouth, its atrophic changes, the appearance of fissures and lobules on the back of the tongue, the development of angular cheilitis, as well as dysbiotic changes. Studies on determining the risk factors for the development of dry mouth syndrome show that cardiovascular disease, gastrointestinal tract, musculoskeletal system, endocrine system, and the intake of some medications are most often attributed to xerostomia. Xerostomia can be of functional and organic origin. Its development is associated with endogenous or exogenous factors. Functional deficiency can be inverse and irreversible. The organic genesis of xerostomia is due to the degeneration of the glandular cells or the complete lack of salivary glands and, in most cases, the process is irreversible. The development of xerostomia is also facilitated by insufficient work or reduction of the number (thinning of the mucous membrane of the oral cavity) of the small salivary glands. In dental practice, the problem of xerostomia is extremely relevant both in connection with the decrease in the quality of life of such patients, and in connection with the effect of this syndrome on the state of the organs of the oral cavity. The saliva carries a protective, regenerative function, provides remineralization of the teeth due to the influx of calcium and phosphorus. It contains components that have antibacterial, antiviral and antifungal effects. Dry mouth contributes to the development of stomatitis, paradontitis, infectious lesions of the mucous membrane of the oral cavity. It is extremely important that the long course of xerostomia with weakly clinically symptomatic leads to untimely treatment of patients for medical assistance. In addition, an integrated approach to the application of different approaches to the prevention of oral mucosal diseases in patients with dry mouth syndrome is an effective method for reducing the risk of developing cancers of the oral cavity Thus, today xerostomia is a topical issue faced by doctors. Secretory activity of the salivary glands has a very important role in providing homeostasis and microbiocinosis of the oral cavity, which affects both the emergence of dental pathology and the overall physical health of humans.